(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study was motivated by the importance of utilising local culture as a context for mathematics learning through an ethnomathematics approach. One cultural artefact that is still used by the people of East Nusa Tenggara is the padalu, or traditional water jar. This study aims to identify and analyse the mathematical elements contained in the padalu as a potential source of contextual mathematics learning. The research method used was descriptive qualitative with data collection techniques in the form of direct observation of the shape of the padalu, measurement of its parts, and visual documentation. Data analysis was carried out by linking the results of observations and measurements with relevant mathematical concepts. The results showed that the padalu represents a combination of a cylindrical shape and a hemisphere. It contains geometric and measurement concepts, such as radius, diameter, height, surface area, volume, symmetry, and size comparison. These findings indicate that padalu has strong potential to be used as a medium for contextual and meaningful local culture-based mathematics learning. Thus, the integration of padalu in mathematics learning can help students understand abstract concepts through real experiences that are close to their daily lives.